Makna Upacara Koke Bale pada Masyarakat Desa Lewomuda - Pulo Betan, Fransiska; Pande, Rikardus; Wai Lawet, Pilipus (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to describe the meaning of the koke bale ceremony in Lewomuda Village, Demon Pagong District. Koke bale is a series of traditional ceremonies that are carried out before the community prepares the land to start the planting process. The theory used in Koke Bale's research is semantic theory. This study also uses qualitative methods supported by data collection techniques, namely interviews, observation and documentation. The results of this study indicate that the koke bale ceremony is a traditional ceremony held in Lewomuda Village, Demon Pagong District. There are eleven important parts in the process of carrying out the koke bale ceremony, namely: kote mada, take koke, tane tenane, take tada, mara, towe lodge, ura mau, butung kewura, goleng, eat together, and hode ilu. In the koke bale ceremony, there are five meanings namely, (1) religious meaning, (2) brotherhood meaning, (3) respect meaning, (4) success meaning, and (5) self-protection meaning.